MOBA게임 캐릭터의 스킨 사용감이 유저에게 미치는 영향연구 -리그 오브 레전드 중심으로 - 이정; Li Jing; 조동민; Cho Dong Min (기초조형학연구, 2018)
본 연구의 목적은 MOBA게임 캐릭터의 스킨 리노베이션 요소를 추출하여 MOBA게임 캐릭터 스킨 리노베이션을 하는 디자이너들에게 좋은 방향과 범위를 제시하고, 이어서 추출한 MOBA게임 캐릭터 스킨 리노베이션의 요소를 통해 가설을 설정하고 유저들에게 적용하여 어떤 요소가 유저들의 게임 체험에 영향을 주는지를 밝히고자 한다. 먼저, 588개 캐릭터 스킨의 연구 대상을 걸쳐 요소를 추출한 결과 크게 변화요소와 유지요소로 나누었다. 다음으로 변화요소를 시각요소(복장, 헤어스타일, 무기외관, 피부, 프랍)와 감각요소(VFX, 캐릭터 모션, 음성효과)로 분류하였다. 이어서 추출한 8개의 변화요소를 MOBA 일반, 오락게임과 MOBA 랭킹, 경기게임을 대응 변수로 가설에 적용하여 최종 8가지의 연구가설을 설정하였다. 그리고 8가지의 연구가설을 검증하기 위해 87명의 응답자를 대상으로 설문조사를 실시하였다. 설문 데이터를 대응표본 t검정으로 일반, 오락게임 할 때와 랭킹, 경기게임 할 때 유저들이 요소에 대한 중요도 차이를 비교 분석하였다. 분석 결과 요소별 8개의 연구가설은 모두 채택됨으로 게임 유저들은 오락과 경기에서 스킨에 대한 욕구가 많은 차이를 나타냈다. 따라서 MOBA게임 유저를 위한 캐릭터 스킨 리노베이션은 정확히 사용자의 게임 목적이 오락 혹은 경기인지를 잘 판단하고 디자인을 실시해야한다. 마지막 결론으로 MOBA게임 유저는 일반게임과 랭킹게임을 목적으로 플레이시 캐릭터 스킨 리노베이션 요소에 대한 중요도가 달라졌다. 일반, 오락게임을 할 때에 유저들의 스킨의 요소에 대한 중요도는 비교적 높은 것으로 알려졌고, 랭킹, 경기게임에서 유저의 중요도 평가는 모든 요소가 3점 이하로 일반, 오락게임 할 때와는 달리 중요하지 않다고 밝혀졌다. The purpose of this study is to present a good direction and scope for designers who perform skin renovation of MOBA game characters by extracting the skin renovation factors of MOBA game character. It is to determine hypotheses through the elements of the extracted MOBA game character skin renovation and to clarify what factors effect the user's game experience by applying them to the users. Firstly, the elements of 588 character skins were extracted from research subjects, which could be divided into the changing factors and maintenance factors. Next, changing factors were classified as visual elements and sensory elements. Secondly, the final 8 research hypotheses were set by applying the extracted factors to the hypotheses using MOBA normal game and rank game as the corresponding variables. In order to verify the 8 research hypotheses, 87 subjects were surveyed. The survey data were compared and analyzed by paired t-test to figure out the differences that users put significance on the elements when they play a normal game and when they play a rank game. The analysis results showed that all of the 8 research hypotheses are adopted. The game users show a great difference in the desire for the skin in the normal game and the rank game. Therefore, the character skin renovation for the MOBA game users must be administered according to the purposes of users, whether for entertainment or for competition. Finally, MOBA game users have placed a different level of importance on the character skin renovation elements according to the purpose of their game such as normal or rank. When the users do normal game, the skin element is quite important, while when they do rank game, the importance of skin is dropped down under 3. Thus, it indicate that the rank game users do not place much importance on it unlike normal game users.